The Effect of Continuous Education Through Audiovisual Media on Knowledge and Attitudes Regarding Treatment Discontinuation Prevention Among Tuberculosis Patients at Community Health Center in East Jakarta in 2024: Pengaruh Edukasi Berkelanjutan Melalui Audio Visual Terhadap Pengetahuan dan Sikap Pencegahan Putus Obat Pasien Tuberkulosis Di Puskesmas Wilayah Jakarta Timur Tahun 2024 - Fitriannur Khasanah, Desvita; Nurulhuda, Uun; Manurung, Suryani (Essential English Grammar, 2024)
The incidence of treatment discontinuation among tuberculosis (TB) patients in DKI Jakarta has been increasing each year. In 2016, a total of 78 patients, or 21.2% of the total number of patients, discontinued their treatment. This study aims to analyze the effect of continuous education through audiovisual media on the knowledge and attitudes regarding the prevention of treatment discontinuation among TB patients.This research employed a quasi-experimental design with a pretest-posttest control group. The inclusion criteria were: patients diagnosed with tuberculosis, patients undergoing treatment for newly diagnosed TB, and patients who had access to social media platforms. The study was conducted from May 20 to July 5, 2024, in the Jatinegara and Kramat Jati areas of East Jakarta. The data instruments used included demographic questionnaires, knowledge questionnaires, attitude questionnaires, and educational modules. A total of 52 respondents participated, with 26 in the intervention group and 26 in the control group. The sampling technique was purposive sampling. Data analysis was performed using SPSS, with the Friedman test followed by the Wilcoxon test. Statistical analysis revealed a p-value of 0.000, which is less than 0.05.  Conclusion: There is a significant effect of continuous audiovisual education on the prevention of treatment discontinuation in TB patients, leading to improvements in both knowledge and attitudes. Further research is recommended to be conducted on TB patients with drug resistance and to include confounding factors such as smoking habits.